Molecular imaging of myocardial fibroblast activation in patients with advanced aortic stenosis before transcatheter aortic valve replacement: a pilot study - Diekmann, Johanna Gesa-Maria; Neuser, Jonas; Röhrich, Manuel; Derlin, Thorsten; Zwadlo, Carolin Tessa; König, Tobias; Weiberg, Desiree; Jäckle, Felix; Kempf, Tibor; Ross, Tobias L.; Tillmanns, Jochen; Thackeray, James; et al. (Journal of nuclear medicine, 2023)
Using multimodal imaging, we investigated the extent and functional correlates of myocardial fibroblast activation in patients with aortic stenosis (AS) scheduled for transcatheter aortic valve replacement (TAVR). AS may cause myocardial fibrosis, which is associated with disease progression and may limit response to TAVR. Novel radiopharmaceuticals identify upregulation of fibroblast activation protein (FAP) as a cellular substrate of cardiac profibrotic activity.
Online veröffentlicht am 8. Juni 2023
Gesehen am 07.12.2023